UJI SIFAT VIRGIN COCONUT OIL (VCO) HASIL EKSTRAKSI ENZIMATIS TERHADAP BERBAGAI PRODUK MINYAK KELAPA HASIL PUBLIKASI - Ni M. Suaniti; Manuntun Manurung; Nadya Hartasiwi (Jurnal Kimia (Journal of Chemistry), 2014)
A complete mixture of waste unripe peels and leaves derived from papaya (Carica papaya) can be used to obtain enzymatic VCO. Enzymatic VCO has been generated and investigated by several detailed determination. Chemical and physical properties characterization of VCO in this process obtained density then viscosity at temperature 40?C achieved value 909,3 kg/m3 and 26,2094 mm2/s (40?C), whereas physical appearance seen as greenish yellow color, natural fresh coconut scent, free from rancid odor and taste. Iodine value, saponification value, ester value, and % FFA about 5,1601 g Iodine/100 g oil; 271,0596 mg-KOH/g oil; 271,2286 mg-KOH/g oil; 0,1725 %. Degree of VCO purity analyzed by use of TLC separation each for eluent 1 or 2 derived around 0,67 and 0,71, in other experiment standard Rf value for methyl laurate attained 0,74.